Odpowiedzi

Najlepsza Odpowiedź!
2009-10-28T21:18:06+01:00
X - pierwsza liczba
y - druga liczba

x = y - 30% * y
40% * x + 1/3 * y = 4

x = y - 3/10 * y
4/10 * x + 1/3 * y = 4

x = 7/10 * y
4/10 * (7/10 * y) + 1/3 * y = 4

x = 7/10 * y
28/100 * y + 1/3 * y = 4

x = 7/10 * y
84/300 * y + 100/300 * y = 4

x = 7/10 * y
184/300 * y = 4

x = 7/10 * y
y = 4 * (300/184) = 300/46 = 150/23

x = 7/10 * 150/23 = (7 * 15)/23 = 105/23
y = 150/23

Odp. Te liczby to 105/23 oraz 105/23.
P.S. Dużej klamry nie potrafię tutaj zrobić ;)